2022
DOI: 10.18203/2320-1770.ijrcog20220033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autologous platelet rich plasma on anti-mullerian hormone and antral follicle count in sub fertile women with poor ovarian reserve

Abstract: Background: Ovarian aging may be reversible. Platelet rich plasma (PRP) has growth factors that promote cellular proliferation and folliculogenesis. Recently published studies and case reports suggest that ovarian rejuvenation can be done by PRP treatment. The objective of the study was to evaluate the effect of platelet rich plasma on ovarian reserve markers such as anti mullerian hormone (AMH) and antral follicle count (AFC) in sub fertile women with poor ovarian reserve (POR).Methods: The self-controlled qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…AFC is a significant indicator of increased reproductive potential, and the significant improvement of AFC in the present study was similar to other studies. 17,35,36 Use of stem cells to prevent the degradation of follicles in the ovaries is not a recent process, but majority of related studies have mostly been clinical trails, and with animal hosts. [37][38][39] However, use of stem cells have also been observed in human trials as resisting DNA damage of natural aging to improve ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…AFC is a significant indicator of increased reproductive potential, and the significant improvement of AFC in the present study was similar to other studies. 17,35,36 Use of stem cells to prevent the degradation of follicles in the ovaries is not a recent process, but majority of related studies have mostly been clinical trails, and with animal hosts. [37][38][39] However, use of stem cells have also been observed in human trials as resisting DNA damage of natural aging to improve ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study of these women revealed significant rise in AMH and fall in FSH over the next three months. 8 A one year follow up study of these women was undertaken to find out more clinically relevant outcomes like change in menstrual cycle and pregnancy.…”
Section: Introductionmentioning
confidence: 99%